A new genus of the subfamily Metrodorinae (Orthoptera: Tetrigidae) from Vietnam - Storozhenko, Sergey Yu. (Zootaxa, 2013)
The monotypic genus Cleostratoides gen. nov. (type species Cleostratoides exoticus sp. nov. from Vietnam) is described in the subfamily Metrodorinae. New genus is closely related to the genera Mazarredia Bolívar, 1887, Xistrella Bolívar, 1909, Pseudoxistrella Liang, 1991, Orthotettixoides Zheng, 1998 and Bermania Storozhenko, 2012, but easily distinguished from all of them by the lateral ocelli situated just under fastigium of vertex and by the antennal sockets placed distinctly above the lower margin of eyes.